ANALISIS PENGARUH PANGSA PASAR PEMBIAYAAN DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITAS PADA BANK SYARIAH - Sarida Sirait; Santi Panjaitan (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
This research was conducted to examine the analysis of the effect of the financing share and Non Performing Financing (NPF) on the profitability of Islamic Banks in the Indonesia 2016. The data used in this study was obtained from Financial Statements publication of each Sharia Bank on the website of Bank Indonesia. Technique the sampling used was purposive sampling. The sample in this study were 11 banks sharia. The data analysis technique used in this study is regression analysis multiple linear and hypothetical testing. This shows that the available data meets the requirements using multiple linear regression equation models. The results of this study indicate that the independent variable of financing share and Non Performing Financing (NPF) shows a significant influence on the profitability of Islamic Banks in Indonesia in 2016. The ability to provide information from independent variables on profitability in this study amounted to 19.3%, the rest explained by other variables not examined in this study.